SEGMENTING, TARGETING, AND POSITIONING INDUSTRI RUMAH TANGGA KE-RAJINAN BAMBU DI KELURAHAN KINILOW KECAMATAN TOMOHON UTARA (Segmenting, Targeting and Positioning The Household Industry of Bamboo Crafts in Kinilow North Tomohon) - Claudia A. A. Undap; Leonardus R. Rengkung; Audrey J. M. Maweikere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aims to determine the application of segmenting, targeting and positioning in the Kinilow bamboo handicraft home industry. This research was conducted from December to February 2020. The data used in this study are primary data and secondary data. Primary data taken from Kinilow home industry players is related tomeasure ments segmenting, targeting and positioning which are qualitative data. Secondary data taken in this study, are related to research and industry players Kinilow. The results of this research shows that in consumers segmenting with psychographicand behavioristic with segmentning selected to determine targeting is behaviolistic because they had advantages such as knowledge of the product itself with good sales results because the actors know the advantages of the product being sold. Positioning is done by looking at the position according to attributes, according to benefits, according to use, according to competitors, and according to price. Because of this measure, consumers understand the product and the positioning issuccessful.Â Keywords : Segmenting, Targeting, and Positioning